Preparation of Plasmonic Ag@PS Composite via Seed-Mediated In Situ Growth Method and Application in SERS - Tian, Xiaoran; Yu, Qian; Kong, Xianming; Zhang, Miao (Frontiers in Chemistry, 2022)
The colloidal polystyrene (PS) was synthesized and decorated with silver nanoparticles (Ag NPs). The plasmonic Ag@PS nanocomposite was prepared by loading Ag NPs on PS microsphere through a seed-mediated in situ growth route. The property of Ag NPs deposited on the PS microsphere could be precisely controlled by adjusting the concentration of the chemicals used in the growth medium. The growth step is only limited by the diffusion of growing species in the growth media to the surface of the Ag seed. The Ag@PS prepared via the in situ growth method exhibited two advantages compared with the self-assembled PS/Ag. First, the high-density of Ag NPs were successfully deposited on the surface of PS as the electroless-deposited Ag seed process, which brings nearly three times SERS enhancement. Second, the rapid preparation process for in situ growth method (half an hour, 10 h for the self-assembled method). The PS/Ag could detect Nile blue A (NBA) down to 10–7 M by SERS. Furthermore, the plasmonic Ag@PS SERS substrate was used for pesticide identification. The on-site monitoring malachite green (MG) from fish was achieved by portable Raman spectrometer, and the limit of detection (LOD) was 0.02 ppm. The Ag@PS substrate has also shown capability for simultaneously sensing multiple pesticides by SERS.